Vestibular evoked myogenic potential - Felipe, Lilian; Kingma, Herman; Gonçalves, Denise Utsch (International Archives of Otorhinolaryngology, 2012)
Introduction: The Vestibular Evoked Myogenic Potential (VEMP) is a promising test for the evaluation of the cholic descending vestibular system. This reflex depends of the integrity from the saccular macula, from the inferior vestibular nerve, the vestibular nuclei, the vestibule-spinal tract and effectors muscles. Objective: Perform a systematic review of the pertinent literature by means of database (COCHRANE, MEDLINE, LILACS, CAPES). Conclusion: The clinical application of the VEMP has expanded in the last years, as goal that this exam is used as complementary in the otoneurological evaluation currently used. But, methodological issues must be clarified. This way, this method when combined with the standard protocol, can provide a more widely evaluation from the vestibular system. The standardization of the methodology is fundamental criterion for the replicability and sensibility of the exam.